Bitcoin is not the new gold - Alexander Kriwoluzky; Christoph Schneider (DIW Weekly Report, 2025)
The price of cryptocurrency Bitcoin has risen sharply over the past ten years, with many investors adding Bitcoin to their portfolios, benefitting from price increases and diversifying their investments. But is Bitcoin suitable for this purpose? This Weekly Report examines the extent to which Bitcoin, like gold, can contribute to the diversification of an investment portfolio. To achieve this, we have calculated the correlation of monthly returns over the last ten years between U.S. and German stocks, bonds, gold, and Bitcoin. The results of our calculations indicate that, unlike gold, Bitcoin has shown a high correlation with stock market returns over time. As a result, an investment portfolio heavily weighted towards stocks cannot achieve the same level of diversification with Bitcoin as it could with gold.
Keywords: E44; G11; G12; 330; Bitcoin; portfolio diversification; financial markets; correlation analysis